The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/bdrb.20063
|View full text |Cite
|
Sign up to set email alerts
|

Two generation reproduction study of ethylbenzene by inhalation in Crl‐CD rats

Abstract: BACKGROUND: This study was conducted to evaluate the potential adverse effects of ethylbenzene (EB) on reproductive capability from whole-body inhalation exposure of F 0 and F 1 parental animals. METHODS: Four groups of Crl:CD(SD)IGS BR rats (30/sex/group for F 0 and 25/sex/group for F 1 ) were exposed to 0, 25, 100, and 500 ppm EB for 6 hr/day for at least 70 consecutive days before mating. Inhalation exposure for the F 0 and F 1 females continued throughout mating, gestation through gestation day (GD) 20, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…Several reproductive and developmental toxicity studies of ethylbenzene have been reported previously Hardin et al, 1981;Ungvary and Tatrai, 1985;Saillenfait et al, 2003;Faber et al, 2006). Narcotic effects from acute inhalation exposures have been reported in male rats exposed to 2180 ppm ethylbenzene (Molnár et al, 1986) and mice exposed to 2000 ppm ethylbenzene (Tegeris and Balster, 1994).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Several reproductive and developmental toxicity studies of ethylbenzene have been reported previously Hardin et al, 1981;Ungvary and Tatrai, 1985;Saillenfait et al, 2003;Faber et al, 2006). Narcotic effects from acute inhalation exposures have been reported in male rats exposed to 2180 ppm ethylbenzene (Molnár et al, 1986) and mice exposed to 2000 ppm ethylbenzene (Tegeris and Balster, 1994).…”
Section: Introductionmentioning
confidence: 90%
“…In addition to these standard assessments within the two-generation study, blood samples were collected on lactation day (LD) 4 and 22 from a subset of F 1 -generation dams as well as from culled F 2 offspring from those dams on postnatal day (PND) 4 and an additional pup/gender/litter (not selected to continue on study in the developmental neurotoxicity component) from those dams after weaning and a single day of direct exposure to ethylbenzene on PND 22. The results concerning the reproductive outcome of the ethylbenzene two-generation toxicity study as well as maternal and offspring blood levels of ethylbenzene have been reported previously (Faber et al, 2006). In most inhalation reproductive toxicity studies that do not include whole body exposures of entire litters, maternal inhalation exposures are stopped temporarily from gestation day (GD) 20 through LD 4.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations